AGENCY REPRESENTATIVE APPLICATIONS WEBSITE DESIGN STUDENTS STMIK JAKARTA STI & K USING PHP & MYSQL - Caryadi Caryadi; Cut Asiana Gemawaty. Skom. MMSi Cut Asiana Gemawaty. Skom. MMSi (Jurnal Sistem Informasi, 2006)
Media information is a means to convey a beruta or information that we received,both orally and in writing, and various kinds such as newspapers, television, radioand computers.Internet is one medium of information very quickly. Certainly much neededinformation is information that is very fast, accurate, and reliable authenticity.Student Representative Body (BPM) is one of the student information center andaspirations STMIK STI & K. Jakarta For the implementation can be used server sidescripting programming language PHP (Personal Home Page) for information on thesite can be accessed through the Internet and take advantage of MySQL software sothat the contents of this site more interesting and dynamic.With the expected student BPM website STMIK Jakarta STI & K can get informationand channel their aspirations.